The level of community knowledge about the use of antibiotics - Hajar Sugihantoro; Ismea Munawaroh; Fidia Rizkiah Inayatillah; Yen Yen Ari Indrawijaya (Universitas Ahmad Dahlan, 2023)
Knowledge and use of antibiotics play a large and important role in the success of treatment, so that they do not cause negative effects, such as the cause of antibiotic resistance. The purpose of this study was to determine the profile and level of knowledge of the community regarding the use of antibiotics in Banyior Village, Sepulu District, Bangkalan Regency, East Java, Indonesia. This research is a cross-sectional descriptive study. The measurement is a closed questionnaire. Data were analyzed using SPSS version 18. The survey was conducted from October 2021 to December 2022 on 325 residents of Banyior Village. The result is that the antibiotic most often used by respondents is amoxicillin with a percentage of 47%. The majority of respondents, 45 percent, get antibiotics from drugstores or stalls. The knowledge level of the general public shows a good level of knowledge of 6.82%, an average level of knowledge of 19.60% and a low level of knowledge of 73.57%. The most widely used antibiotic by respondents in this study was amoxicillin, where the most common way to obtain it was through drug stores/stalls and public knowledge of the use of antibiotics was still low.